Immune Response and Mechanisms of IFN-γ in Administration for Keratomycosis. (18th August 2019) - Zheng, Xuedong; Xie, Tianlu; Lin, Yan; Yang, Juan; Huang, Libin; Zhang, Jingjin; Han, Xiaoli; Hu, Jianzhang
ABSTRACT: Purpose : To investigate the immune response and mechanisms of interferon-γ (IFN-γ) in the fungal keratitis in mice. Methods : Mice were divided into two groups: group A, topical PBS four times daily post-infection; group B: topical IFN-γ four times daily post-infection. At1, 3, 5, and 7 days, the corneal lesions and inflammatory responses were observed by slit lamp, and immunofluorescence staining was performed to evaluate F4/80+ and CD4+ cells. Using ELISA, and RT–PCR to detect the expression levels of macrophage migration inhibitory factor (MIF), macrophage inflammatory protein-2 (MIP-2), IL-4, IL-10, IL-12, and IFN-γ. Results : The treatment with IFN-γ decreased clinical scores and expression levels of IL-4, increased expression of F4/80+ and CD4+ cells, whereas IL-12, MIF, and MIP-2 were expressed highly, and the peaks of IL-10 and IFN-γ move forward. Conclusion : This experiment showed that IFN-γ eye drops increase the accumulation of macrophages and shorten the duration of fungal keratitis.